Thermal properties of cubic zincblende thallium-phosphide from quasi-harmonic Debye model approximation - Daoud, Salah (International Journal of Physical Research, 2017)
The thermal properties of cubic zincblende (B3) thallium - phosphide (TlP) compound under high pressure up to 12 GPa have been studied using the quasi-harmonic Debye model approximation. The relative unit cell volume, the isothermal bulk modulus, the first order derivative isothermal bulk modulus, the Debye temperature and the Grüneisen parameter are studied at zero-temperature and at standard ambient temperature (298 K) respectively. Our obtained values of the different previous quantities are in general in agreement compared to other theoretical data of the literature.